HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN WASTING PADA ANAK DIBAWAH DUA TAHUN DI KABUPATEN ACEH BESAR - , Nurzahara; , Prof. dr. Djauhar I., SpA(K)., MPH., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Wasting is still a cause of child mortality and morbidity. Globally, wasting in infants less than six months of age reaches 8.5 million cases. Exclusive breastfeeding is believed as one of the efforts to reduce wasting in which breastfeeding is given for six months after birth. In Indonesia, wasting among under-five children has reached 13.6% while in Aceh Besar District it reaches 15.71% with a decreased coverage of exclusive breastfeeding in these past three years. Objective: To find out the association between exclusive breastfeeding and incidence of wasting among under-two children in Aceh Besar District. Method: This was an observational study with matching case control design. The population was all under-two children living in Aceh Besar District. The samples were under-two children ranging from 7 to 24 months of age. The sample taking used two stage cluster random sampling and purposive sampling resulting in a sample size of 70 children comprising 35 cases and 35 controls. The bivariable analysis used chi-square (c 2 ) McNemar and the multivariable analysis used conditional logistic regression. Result: Based on the bivariable analysis, there was a significant association statistically between non exclusive breastfeeding and incidence of wasting in under-two children (p = 0,0290